BIJI SAWIT SEBAGAI MOTIF PADA HANDBAG WANITA - Julia Dwi Sasmita; Ahmad Bahrudin (Relief : Journal of Craft, 2021)
This article is an idea of creating women's handbags which are carried out according to the method of creating works of art, namely exploration, design, and embodiment. In the exploration stage, the activities carried out are market observations and digging references from various sources of knowledge. The next stage is the design, which is built based on the analysis obtained, followed by visualizing the idea in the form of a sketch as a reference for working drawings in the process of realizing this women's handbag or handbag product. The result of the creation of this bag consists of 2 women's handbags or handbags with attractive shapes. This bag is bolted with a hand sewing technique without using a machine and using a knot and basting technique.ABSTRAKArtikel ini adalah sebuah gagasan penciptaan karya kriya tas tangan wanita yang dilakukan sesuai dengan metode penciptaan karya seni yaitu eksplorasi, perancangan, dan perwujudan. Dalam tahap eksplorasi kegiatan yang dilakukan adalah pengamatan pasar dan menggali referensi dari berbagai sumber pengetahuan. Tahap selanjutanya adalah perancangan, yang dibangun berdasarkan perolehan analisis, diteruskan dengan memvisualisasikan gagasan berbentuk sketsa sebagai acuan gambar kerja dalam proses perwujudan produk tas atau handbag wanita ini . Hasil dari penciptaan tas ini terdiri dari 2 tas atau handbag wanita dengan bentuk yang menarik. Tas ini dibaut dengan teknik jahit tangan tidak menggunakan mesin dan menggunakan teknuk sulam simpul dan jelujur.